POWER SPECTRAL DENSITY ANALYSIS OF STEEL SURFACE TOPOGRAPHY CHANGE ON A BOUNDARY LUBRICATED RECIPROCATING SLIDING CONTACT - Jamari, Jamari (ROTASI, 2008)
Study the change of the surface topography using spectral density analysis was done by performing experiments on ball-on-plate steel under boundary lubricated reciprocating sliding contact. Measurement of the surface topography was executed by an optical profilometer: Micromap 512. Matching and Stitching computer code method was employed in order to get more detailed information about the surfaces before and after the experiment. The profile evolutions of the surface for a certain number of running cycles were presented on the PSD (Power Spectral Density) and spatial frequency form. In the analysis, results show that the surface changes more in the running direction than in the traverse direction.